2009
DOI: 10.2223/jped.1932
|View full text |Cite
|
Sign up to set email alerts
|

Prone position and reduced thoracoabdominal asynchrony in preterm newborns

Abstract: Objective: To assess the effect of prone and supine positions on breathing pattern variables, thoracoabdominal motion and peripheral oxygen saturation of hemoglobin of premature newborn infants recovering from respiratory distress syndrome, while breathing spontaneously and in rapid eye movement sleep. Methods:This was a quasi-experimental study. Twelve preterms weighing > 1,000 g at enrollment were studied in both positions, in random order. Respiratory inductive plethysmography was used to analyze breathing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“…The former assessed between 8 and 15 breaths for each subject, whereas we assessed, on average, 215 cycles per child. Authors examining a large number of respiratory cycles also observed high values of standard deviation of the variables for thoracoabdominal motion 17, 18, 25…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The former assessed between 8 and 15 breaths for each subject, whereas we assessed, on average, 215 cycles per child. Authors examining a large number of respiratory cycles also observed high values of standard deviation of the variables for thoracoabdominal motion 17, 18, 25…”
Section: Discussionmentioning
confidence: 95%
“…This is a noninvasive method that requires little effort from the individual. The measures are based on changes in the cross‐sectional area of the chest wall and are captured by two bands of inductance,16 one positioned in the axilla and the other placed in the umbilical line, according to established criteria 10, 17, 18. The devices provide breath waveform sampling at 50 points/sec.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 Comparison of the decrease in gastric residuals in the supine and prone positions at feeding volumes of 50 ml/kg/day (stage 1) and 100 ml/kg/day (stage 2). and hypoxia, and better thoracoabdominal synchrony (Oliveira et al, 2009). Infants sleeping in the prone position also have higher surface temperatures and narrower central to peripheral temperature gradients (Ammari et al, 2009), and can sleep for longer, as well as experience fewer awakenings and arousals per hour, with a greater sleep efficiency (Myers et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The mean rates were very similar, with a variation of less than one breath per minute between the four decubitus positions, and no significant difference was observed between positions. Studies have shown that body position does not interfere with respiratory rate in clinically stable preterm or full-term newborns (3,22). However, body position was found to exert an effect on the respiratory rate of preterm newborns during sleep, in infants receiving supplemental oxygen and during gavage feeding, with lower variability and lower mean values being observed in the prone position (3,6,(10)(11)(12)23).…”
Section: Discussionmentioning
confidence: 99%